2012
DOI: 10.1097/mph.0b013e31823dd370
|View full text |Cite
|
Sign up to set email alerts
|

Extraneural Metastasis of a Nongerminomatous Germ Cell Tumor of the Central Nervous System in a Pediatric Patient With a Ventriculoperitoneal Shunt

Abstract: We describe the case of a 7-year-old white boy who presented with a mixed malignant germ cell tumor with predominant embryonal carcinoma component. The patient underwent right ventriculoperitoneal (VP) shunt placement for hydrocephalus at the time of diagnosis. He received multiagent chemotherapy followed by second-look surgery. Despite an initial response to chemotherapy, the patient had metastatic progression of disease within the craniospinal axis. He received craniospinal radiation and high-dose chemothera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Our case report and review of the literature revealed 28 cases 1–22 of central nervous system tumors demonstrating evidence of extraneural spread associated with VPS in children. In patients of widely varying ages and similar gender distributions a wide variety of tumors were reported, with medulloblastomas and pineal tumors cited most commonly.…”
Section: Discussionmentioning
confidence: 76%
“…Our case report and review of the literature revealed 28 cases 1–22 of central nervous system tumors demonstrating evidence of extraneural spread associated with VPS in children. In patients of widely varying ages and similar gender distributions a wide variety of tumors were reported, with medulloblastomas and pineal tumors cited most commonly.…”
Section: Discussionmentioning
confidence: 76%
“…Thirty-eight articles with a total of 43 patients were reviewed [ Table 1 ]. [ 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 ] The mean age of patients was 15 years and 3 months, with 69.8% (30 out of 43) of the patients in the pediatric age group (<18 years of age), and 67.4% male (29 out of 43). The overall predominant histological subtypes of primary CNS tumors with VPS-related metastasis were germinomas (11 out of 43, 25.6%) and medulloblastomas (5 out of 43, 11.6%).…”
Section: Discussionmentioning
confidence: 99%
“…Only 10 patients developed EIM, 2 of whom were diagnosed with GCTs, 6 with neural tube cell tumors, 1 with ependymoma, and 1 with an atypical rod-shaped tumor. Another study by Belongia and Jogal [ 7 , 8 ] reported that only 0.98% of patients with primary intracranial tumors developed EIM. In addition, Kun et al [ 9 ] recently reported 2 cases of pineal tumors.…”
Section: Discussionmentioning
confidence: 99%